KUALITAS FISIKOKIMIA DAN SENSORIS BISKUIT SPEKULAAS BERBAHAN DASAR TEPUNG KOMPOSIT PISANG GOROHO (Musa Acuminate) DAN UBI JALAR UNGU (Ipomoae batatas L) - Amalia Regina Mokodompit; Erny J.N. Nurali; Thelma D.J. Tuju (COCOS, 2017)
ABSTRACTSpeculaas is one type of biscuits that in the making using spice herbs such as cinnamon, nutmeg and cloves that provide a very specific aroma blend. This research aims to get the mixture formula of goroho flour and purple sweet potato flour which is right on Spekulaas biscuit making. This study used a Completely Randomized Design (RAL) with 4 treatments ie A (62.5% goroho flour: 37.5% purple sweet potato flour), B (75% goroho flour: 25% purple sweet potato flour), C (82.5 % goroho flour: 12.5% purple sweet potato flour), D (50% goroho flour: 50% purple sweet potato flour). Each treatment consisted of 3 replications. From the results of this study it can be concluded that Spekulaas biscuits made from composite flour 62.5% goroho flour : 37.5% purple sweet potato flour is the most preferred biscuit panelist that has a level of biscuit hardness 29.33 mm / g / sec, carbohydrate 64, 45%, fat 22.94%, water content 5.72%, 4.74% protein, ash content 2.15% and contains 483.22 kcal calories.Keywords: biscuit, composite flour, goroho banana, purple sweet potato